Integration of variable photosynthetic capacity into a biogeochemical model - Straube, Jonathan R., author; Ojima, Dennis S., advisor; Parton, William J., committee member; Burns, Patrick J., committee member (Colorado State University. Libraries, 2011)
We integrated a photosynthetic sub-model into the daily Century model, DayCent, to improve the estimations of carbon fluxes at the Niwot Ridge LTER site; the new version is called DayCent-Photosyn. The photosynthetic sub-model, adapted from the SIPNET/PnET family of models, includes solar radiation and vapor pressure deficit controls on production, as well as temperature and water stress terms. A key feature we added to the base photosynthetic equations is the addition of a variable maximum net photosynthetic rate (Amax). We optimized the parameters controlling photosynthesis using a variation of the Metropolis-Hastings algorithm along with data-assimilation techniques. The model was optimized and validated against level 4 data available from the Ameriflux website using observed net ecosystem exchange (NEE) and estimated gross primary production (GPP) and ecosystem respiration (Re) values. The inclusion of a variable Amax rate greatly improved model performance (NEE RMSE = 0.63 gC m-2, AIC= 2099) versus a version with a single Amax parameter (NEE RMSE = 0.74 gC m-2, AIC= 3724). DayCent-Photosyn is able to capture the inter-annual and seasonal flux patterns, including the critical early season assimilation, but tends to overestimate yearly NEE uptake. The simulated influence of a variable Amax rate suggest a need for further studies on the process controls affecting the seasonal photosynthetic rates.
Keywords: DayCent; photosynthesis; Niwot Ridge; Amax